Significance of osteopontin expression in human invasive breast tumour stroma - Rodrigues, L. R. (2009)
Osteopontin has been reported to stimulate cell adhesion, migration and specific signalling functions. Its overexpression has been found in melanoma, breast, lung, colorectal, stomach and ovarian cancer. However, its overexpression and role in human breast cancer remains to be elucidated. In this study, invasive breast tumours from 129 patients were examined by immunohistochemistry in order to assess osteopontin association with several molecular tumour markers. Additionally, its relationship with proliferation and angiogenesis was determined. Ultimately, other tumour variables such as histological grade, tumour size and nodal status were also assessed. Results achieved showed that no statistical significant association exists between osteopontin expression and major clinicopathological parameters or angiogenesis, except for the number of lymph nodes involved. However, a correlation with some molecular markers was observed, namely with P-Cadherin, EGFR, cytokeratin 14 and vimentin. Additionally, higher proliferation rates were found for the tumours expressing osteopontin. Although several studies refer osteopontin as a potential breast cancer biomarker, it is still not clear if it can provide important diagnosis information, evaluate treatment effects or assess the potential for metastatic disease in patients.